The Effect Of Placement, Material Incentives And Non Material Incentives On Employee Job Satisfaction (Study Of Non-Medical Employees Of RSJT Pekanbaru In Indonesia) - Kasmiruddin, Kasmiruddin; Ruzikna, Ruzikna; Othman, Lie; Mandataris, Mandataris; Nurfitri, Nurfitri (Publisher Cv. Inara, 2024)
This study aims to analyze whether there is a simultaneous and partial influence of employee reward variables, material incentives and non-material incentives on job satisfaction at RSJT Pekanbaru Hospital. The research method used is quantitative, namely research that aims to explain the relationship between employee placement variables, material incentives and non-material incentives and job satisfaction variables. All research variables are reduced to several research indicators and indicators are reduced to research instruments. The research population was all staff of the General Administration and Finance Section of RSJT, totaling 72 people. Considering the population was less than 100, the entire population was used as respondents. To collect data using a questionnaire distribution technique, with the consideration that respondents did not have time to be interviewed and were able to understand the substance of the questionnaire. The analytical technique used to analyze research data is the Multiple Liner Regression statistical technique and uses SPSS version 22. From the research results it was found that employee placement has a significant effect on job satisfaction of RSJT non-medical employees; providing material incentives has a significant effect on job satisfaction of RSJT non-medical employees; providing non-material incentives has a significant effect on job satisfaction of RSJT non-medical employees; and employee placement, material incentives and non-material incentives have a significant effect on job satisfaction of nonmedical employees together. It is recommended that the leadership of RSJT Pekanbaru, 1) consider the suitability of employee placement with the education, skills and work experience of non-medical employees; 2) Adjusting the provision of material incentives to employee expectations and needs and related to employee morale; 3) Provision of non-material incentives must be in accordance with work performance and employee needs.